Vesicle formation mechanisms: an overview. (2nd January 2021) - Has, Chandra; Pan, Sharadwata
Abstract: Vesicle structures primarily embody spherical capsules composed of a single or multiple bilayers, entrapping a pool of aqueous solution in their interior. The bilayers can be synthesised by phospholipids or other amphiphiles (surfactants, block copolymers, etc.). Vesicles with broad-spectrum applications in numerous scientific disciplines, including biochemistry, biophysics, biology, and various pharmaceutical industries, have attracted widespread attention. Consequently, a multitude of protocols have been devised and proposed for their fabrication. In this review, with a motivation to derive the basic conditions for the formation of vesicles, the associated thermodynamic and kinetic aspects are comprehensively appraised. Contextually, an all-purpose overview of the underlying thermodynamics of bilayer/membrane generation and deformation, including the chemical potential of aggregates, geometric packing and the concept of elastic properties, is presented. Additionally, the current review highlights the probable, inherent mechanisms of vesicle formation under distinct modes of manufacturing. We lay focus on vesicle formation from pre-existing bilayers, as well as from bilayers, which form when lipids from an organic solvent are transferred into an aqueous medium. Furthermore, we outline the kinetic effects on vesicle formation from the lamellar phase, with and without the presence of shearing force. Wherever required, the experimental and/or theoretical outcomes, the driving forces for vesicle size selection, and various scaling laws are also reviewed, all of which facilitate an overall improved understanding of the vesicle formation mechanisms.